If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 19 = -4 Reorder the terms: 19 + 5x = -4 Solving 19 + 5x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 5x = -4 + -19 Combine like terms: 19 + -19 = 0 0 + 5x = -4 + -19 5x = -4 + -19 Combine like terms: -4 + -19 = -23 5x = -23 Divide each side by '5'. x = -4.6 Simplifying x = -4.6
| 14+(-2x)=14 | | r-34=23 | | 10-3y+4y=12 | | 9x^2-3kx+k=0 | | b-85=8 | | h-71=22 | | 3x-12+12=-5x | | 3s^2-2s-40=0 | | x^2-40x-11=0 | | q-22=11 | | 9-22=11 | | 3x+5x-6=150 | | f-45=45 | | 1200=7v^2 | | y-62=5 | | 5x+45=2x+15 | | 3x=-10-2y | | 0.057=0.11(w) | | 4(w-7)-8=-6(4w+5)-5w | | 25-(10-2)= | | p-14=9 | | y=3(x-5)(7-x) | | sqrtx-9=-6 | | w-6.4=2.3 | | 9x-12y=-15 | | g-17=3 | | c-3=18 | | a-5.4=10.2 | | 8m-7=20-m | | y-30=124 | | -4(-6v+3)-2v=4(v-4)-5 | | 4x^2+4x+1=40000 |